In mathematics, a formal series is an infinite sum that is considered independently from any notion of convergence, and can be manipulated with the usual algebraic operations on series (addition, subtraction, multiplication, division, partial sums, etc.).
A formal power series is a special kind of formal series, of the form
infty | |
\sum | |
n=0 |
n=a | |
a | |
0+a |
1x+
2+ … , | |
a | |
2x |
an,
xn
x
A formal power series with coefficients in a ring
R
R.
R
R[[x]].
R[x],
Formal powers series in several indeterminates are defined similarly by replacing the powers of a single indeterminate by monomials in several indeterminates.
Formal power series are widely used in combinatorics for representing sequences of integers as generating functions. In this context, a recurrence relation between the elements of a sequence may often be interpreted as a differential equation that the generating function satisfies. This allows using methods of complex analysis for combinatorial problems (see analytic combinatorics).
A formal power series can be loosely thought of as an object that is like a polynomial, but with infinitely many terms. Alternatively, for those familiar with power series (or Taylor series), one may think of a formal power series as a power series in which we ignore questions of convergence by not assuming that the variable X denotes any numerical value (not even an unknown value). For example, consider the series
A=1-3X+5X2-7X3+9X4-11X5+ … .
If we studied this as a power series, its properties would include, for example, that its radius of convergence is 1 by the Cauchy–Hadamard theorem. However, as a formal power series, we may ignore this completely; all that is relevant is the sequence of coefficients [1, −3, 5, −7, 9, −11, ...]. In other words, a formal power series is an object that just records a sequence of coefficients. It is perfectly acceptable to consider a formal power series with the factorials [1, 1, 2, 6, 24, 120, 720, 5040, ... ] as coefficients, even though the corresponding power series diverges for any nonzero value of X.
Algebra on formal power series is carried out by simply pretending that the series are polynomials. For example, if
B=2X+4X3+6X5+ … ,
then we add A and B term by term:
A+B=1-X+5X2-3X3+9X4-5X5+ … .
We can multiply formal power series, again just by treating them as polynomials (see in particular Cauchy product):
AB=2X-6X2+14X3-26X4+44X5+ … .
Notice that each coefficient in the product AB only depends on a finite number of coefficients of A and B. For example, the X5 term is given by
44X5=(1 x 6X5)+(5X2 x 4X3)+(9X4 x 2X).
For this reason, one may multiply formal power series without worrying about the usual questions of absolute, conditional and uniform convergence which arise in dealing with power series in the setting of analysis.
Once we have defined multiplication for formal power series, we can define multiplicative inverses as follows. The multiplicative inverse of a formal power series A is a formal power series C such that AC = 1, provided that such a formal power series exists. It turns out that if A has a multiplicative inverse, it is unique, and we denote it by A−1. Now we can define division of formal power series by defining B/A to be the product BA−1, provided that the inverse of A exists. For example, one can use the definition of multiplication above to verify the familiar formula
1 | |
1+X |
=1-X+X2-X3+X4-X5+ … .
An important operation on formal power series is coefficient extraction. In its most basic form, the coefficient extraction operator
[Xn]
A
n
[X2]A=5
[X5]A=-11
\begin{align} \left[X3\right](B)&=4,\ \left[X2\right](X+3X2Y3+10Y6)&=3Y3,\\ \left[X2Y3\right](X+3X2Y3+10Y6)&=3,\\ \left[Xn\right]\left(
1 | |
1+X |
\right)&=(-1)n,\ \left[Xn\right]\left(
X | |
(1-X)2 |
\right)&=n. \end{align}
Similarly, many other operations that are carried out on polynomials can be extended to the formal power series setting, as explained below.
If one considers the set of all formal power series in X with coefficients in a commutative ring R, the elements of this set collectively constitute another ring which is written
R[[X]],
One can characterize
R[[X]]
R[X]
R[[X]]
R[[X]]
As a set,
R[[X]]
R\N
R
n
an
(an)
(an)n\in\N+(bn)n\in\N=\left(an+bn\right)n\in\N
and multiplication by
(an)n\in\N x (bn)n\in\N=\left(
n | |
\sum | |
k=0 |
akbn-k\right)n\in\N.
This type of product is called the Cauchy product of the two sequences of coefficients, and is a sort of discrete convolution. With these operations,
R\N
(0,0,0,\ldots)
(1,0,0,\ldots)
The product is in fact the same one used to define the product of polynomials in one indeterminate, which suggests using a similar notation. One embeds
R
R[[X]]
a\inR
(a,0,0,\ldots)
(0,1,0,0,\ldots)
X
(a0,a1,a2,\ldots,an,0,0,\ldots)=a0+a1X+ … +anXn=
n | |
\sum | |
i=0 |
aiXi;
these are precisely the polynomials in
X
(an)n\in\N
style\sumi\in\NaiXi
\left(\sumi\in\Nai
i\right)+\left(\sum | |
X | |
i\in\N |
biXi\right)=\sumi\in\N(ai+bi)Xi
and
\left(\sumi\in\NaiXi\right) x \left(\sumi\in\NbiXi\right)=\sumn\in\N
n | |
\left(\sum | |
k=0 |
akbn-k\right)Xn.
which is quite convenient, but one must be aware of the distinction between formal summation (a mere convention) and actual addition.
Having stipulated conventionally that
one would like to interpret the right hand side as a well-defined infinite summation. To that end, a notion of convergence in
R\N
R\N
R\N
R
R\N
I=(X)
X
a0
(an),(bn)\inR\N,
k
ak ≠ bk
Informally, two sequences
(an)
(bn)
X
an
i=n
Xn
This topological structure, together with the ring operations described above, form a topological ring. This is called the ring of formal power series over
R
R[[X]]
X
The topological structure allows much more flexible usage of infinite summations. For instance the rule for multiplication can be restated simply as
\left(\sumi\in\NaiXi\right) x \left(\sumi\in\NbiXi\right)=\sumi,j\in\NaibjXi+j,
since only finitely many terms on the right affect any fixed
Xn
The above topology is the finest topology for which
infty | |
\sum | |
i=0 |
aiXi
always converges as a summation to the formal power series designated by the same expression, and it often suffices to give a meaning to infinite sums and products, or other kinds of limits that one wishes to use to designate particular formal power series. It can however happen occasionally that one wishes to use a coarser topology, so that certain expressions become convergent that would otherwise diverge. This applies in particular when the base ring
R
In the ring of formal power series
\Z[[X]][[Y]]
Y
\Z[[X]]
infty | |
\sum | |
i=0 |
XYi
converges (and its sum can be written as
\tfrac{X}{1-Y}
infty | |
\sum | |
i=0 |
XiY
would be considered to be divergent, since every term affects the coefficient of
Y
Y
\Z[[X]]
\Z[[X]][[Y]]
Y
X
Y
\tfrac{1}{1-X}
\tfrac{Y}{1-X}
This way of defining the topology is in fact the standard one for repeated constructions of rings of formal power series, and gives the same topology as one would get by taking formal power series in all indeterminates at once. In the above example that would mean constructing
\Z[[X,Y]]
XiYj
I
I=(X,Y)
X
Y
The same principle could be used to make other divergent limits converge. For instance in
\R[[X]]
\limn\toinfty\left(1+
X | |
n |
\right)n
does not exist, so in particular it does not converge to
\exp(X)=\sumn\in\N
Xn | |
n! |
.
This is because for
i\geq2
\tbinom{n}{i}/ni
Xi
n\toinfty
\R
\tfrac{1}{i!}
\exp(X)
\R[[X]]
\R\N
\R
\exp(X)
The ring
R[[X]]
S
R
I
S
I
S
x
I
\Phi:R[[X]]\toS
\Phi
R
\Phi
\Phi(X)=x
One can perform algebraic operations on power series to generate new power series.[1] [2] Besides the ring structure operations defined above, we have the following.
For any natural number, the th power of a formal power series is defined recursively by
If and are invertible in the ring of coefficients, one can prove[3] [4] [5] whereIn the case of formal power series with complex coefficients, the complex powers are well defined for series with constant term equal to . In this case,
f\alpha
f\alpha=\exp(\alphalog(f)),
f(f\alpha)'=\alphaf\alphaf'
(f\alpha)\beta=f\alpha\beta
f\alphag\alpha=(fg)\alpha
The series
A=
infty | |
\sum | |
n=0 |
anXn\inR[[X]]
is invertible in
R[[X]]
a0
R
A
B=b0+b1x+ …
a0b0
A ⋅ B
B
\begin{align} b0&=
1 | |
a0 |
,\\ bn&=-
1 | |
a0 |
n | |
\sum | |
i=1 |
aibn-i, n\geq1. \end{align}
An important special case is that the geometric series formula is valid in
R[[X]]
(1-X)-1=
infty | |
\sum | |
n=0 |
Xn.
If
R=K
X
K[[X]]
X
The computation of a quotient
f/g=h
| ||||||||||
|
infty | |
=\sum | |
n=0 |
cnXn,
assuming the denominator is invertible (that is,
a0
f
g
f=gh
cn=
1 | |
a0 |
\left(bn-
n | |
\sum | |
k=1 |
akcn-k\right).
The coefficient extraction operator applied to a formal power series
f(X)=
infty | |
\sum | |
n=0 |
anXn
in X is written
\left[Xm\right]f(X)
and extracts the coefficient of Xm, so that
\left[Xm\right]f(X)=\left[Xm\right]
infty | |
\sum | |
n=0 |
anXn=am.
Given two formal power series
f(X)=
infty | |
\sum | |
n=1 |
anXn=a1X+a2X2+ …
g(X)=
infty | |
\sum | |
n=0 |
bnXn=b0+b1X+b2X2+ …
a0=0,
g(f(X))=
infty | |
\sum | |
n=0 |
bn(f(X))n=
infty | |
\sum | |
n=0 |
cnXn,
where the coefficients cn are determined by "expanding out" the powers of f(X):
cn:=\sumk\in\N,bk
a | |
j1 |
a | |
j2 |
…
a | |
jk |
.
Here the sum is extended over all (k, j) with
k\in\N
k | |
j\in\N | |
+ |
|j|:=j1+ … +jk=n.
Since
a0=0,
k\len
ji\len
i.
cn
Xn
gn(fn(X))
fn
gn
xn,
X
n.
A more explicit description of these coefficients is provided by Faà di Bruno's formula, at least in the case where the coefficient ring is a field of characteristic 0.
Composition is only valid when
f(X)
cn
f(X)
g(X)
g(f(X))
R[[X]]
Assume that the ring
R
R
\exp(X)
\exp(X)=1+X+
X2 | |
2! |
+
X3 | |
3! |
+
X4 | |
4! |
+ … ,
then the equality
\exp(\exp(X)-1)=1+X+X2+
5X3 | |
6 |
+
5X4 | |
8 |
+ …
makes perfect sense as a formal power series, since the constant coefficient of
\exp(X)-1
Whenever a formal series
f(X)=\sumkfkXk\inR[[X]]
has f0 = 0 and f1 being an invertible element of R, there exists a series
g(X)=\sumkgkXk
that is the composition inverse of
f
f
g
x=0+1x+0x2+0x3+ …
g
Given a formal power series
f=\sumn\geqanXn\inR[[X]],
we define its formal derivative, denoted Df or f ′, by
Df=f'=\sumnannXn-1.
The symbol D is called the formal differentiation operator. This definition simply mimics term-by-term differentiation of a polynomial.
This operation is R-linear:
D(af+bg)=a ⋅ Df+b ⋅ Dg
for any a, b in R and any f, g in
R[[X]].
D(fg) = f ⋅ (Dg)+(Df) ⋅ g,
and the chain rule works as well:
D(f\circg)=(Df\circg) ⋅ Dg,
whenever the appropriate compositions of series are defined (see above under composition of series).
Thus, in these respects formal power series behave like Taylor series. Indeed, for the f defined above, we find that
(Dkf)(0)=k!ak,
where Dk denotes the kth formal derivative (that is, the result of formally differentiating k times).
If
R
R
f=\sumn\geqanXn\inR[[X]],
we define its formal antiderivative or formal indefinite integral by
D-1f=\intf dX=C+\sumnan
Xn+1 | |
n+1 |
.
for any constant
C\inR
This operation is R-linear:
D-1(af+bg)=a ⋅ D-1f+b ⋅ D-1g
for any a, b in R and any f, g in
R[[X]].
D(D-1(f))=f
for any
f\inR[[X]]
R[[X]]
R
R[X]
R
The Jacobson radical of
R[[X]]
X
R
The maximal ideals of
R[[X]]
R
M
R[[X]]
M\capR
R
M
X
M\capR
Several algebraic properties of
R
R[[X]]
R
R[[X]]
R
R[[X]]
R
R[[X]]
K
K[[X]]
The metric space
(R[[X]],d)
The ring
R[[X]]
R[[X]]
See main article: article. The ring of formal power series with coefficients in a complete local ring satisfies the Weierstrass preparation theorem.
Formal power series can be used to solve recurrences occurring in number theory and combinatorics. For an example involving finding a closed form expression for the Fibonacci numbers, see the article on Examples of generating functions.
One can use formal power series to prove several relations familiar from analysis in a purely algebraic setting. Consider for instance the following elements of
\Q[[X]]
\sin(X):=\sumn
(-1)n | |
(2n+1)! |
X2n+1
\cos(X):=\sumn
(-1)n | |
(2n)! |
X2n
Then one can show that
\sin2(X)+\cos2(X)=1,
\partial | |
\partialX |
\sin(X)=\cos(X),
\sin(X+Y)=\sin(X)\cos(Y)+\cos(X)\sin(Y).
The last one being valid in the ring
\Q[[X,Y]].
For K a field, the ring
K[[X1,\ldots,Xr]]
In mathematical analysis, every convergent power series defines a function with values in the real or complex numbers. Formal power series over certain special rings can also be interpreted as functions, but one has to be careful with the domain and codomain. Let
f=\sumanXn\inR[[X]],
and suppose
S
R
I
S
S
x
I
f(x)=\sumn\geanxn.
This series is guaranteed to converge in
S
x
(f+g)(x)=f(x)+g(x)
and
(fg)(x)=f(x)g(x).
Unlike in the case of bona fide functions, these formulas are not definitions but have to be proved.
Since the topology on
R[[X]]
(X)
R[[X]]
(X)
f(0)
f(X2-X)
f((1-X)-1-1)
f\inR[[X]].
With this formalism, we can give an explicit formula for the multiplicative inverse of a power series
f
a=f(0)
R
f-1=\sumna-n-1(a-f)n.
If the formal power series
g
g(0)=0
f(g)=X
where
f
f(0)=0
g
The formal Laurent series over a ring
R
f=
infty | |
\sum | |
n=N |
anXn
for some integer
N
n
an ≠ 0
n
an ≠ 0
f
\operatorname{ord}(f).
+infty
Multiplication of such series can be defined. Indeed, similarly to the definition for formal power series, the coefficient of
Xk
\{an\}
\{bn\}
The formal Laurent series form the ring of formal Laurent series over
R
R((X))
R[[X]]
X
R=K
K((X))
K[[X]]
As with
R[[X]]
R((X))
One may define formal differentiation for formal Laurent series in the natural (term-by-term) way. Precisely, the formal derivative of the formal Laurent series
f
f
n
R
Assume that
K
D\colonK((X))\toK((X))
defined above is a
K
\kerD=K
\operatorname{im}D=\left\{f\inK((X)):[X-1]f=0\right\}.
The latter shows that the coefficient of
X-1
f
f
\operatorname{Res}(f)
\operatorname{Res}:K((X))\toK
is
K
0\toK\toK((X))\overset{D}{\longrightarrow}K((X)) \overset{\operatorname{Res}}{\longrightarrow} K\to0.
Some rules of calculus. As a quite direct consequence of the above definition, and of the rules of formal derivation, one has, for any
f,g\inK((X))
\operatorname{Res}(f')=0;
\operatorname{Res}(fg')=-\operatorname{Res}(f'g);
\operatorname{Res}(f'/f)=\operatorname{ord}(f), \forallf ≠ 0;
\operatorname{Res}\left((g\circf)f'\right)=\operatorname{ord}(f)\operatorname{Res}(g),
\operatorname{ord}(f)>0;
[Xn]f(X)=\operatorname{Res}\left(X-n-1f(X)\right).
Property (i) is part of the exact sequence above. Property (ii) follows from (i) as applied to
(fg)'=f'g+fg'
f
f=Xmg
m=\operatorname{ord}(f)
\operatorname{ord}(g)=0
f'/f=mX-1+g'/g.
\operatorname{ord}(g)=0
g
K[[X]]\subset\operatorname{im}(D)=\ker(\operatorname{Res}),
\operatorname{Res}(f'/f)=m.
\operatorname{im}(D)=\ker(\operatorname{Res}),
g=g-1X-1+G',
G\inK((X))
(g\circf)f'=g-1f-1f'+(G'\circf)f'=g-1f'/f+(G\circf)'
See main article: Lagrange inversion theorem. As mentioned above, any formal series
f\inK[[X]]
g\inK[[X]].
k[Xk]gn=n[X-n]f-k.
In particular, for n = 1 and all k ≥ 1,
[Xk]g=
1 | |
k |
\operatorname{Res}\left(f-k\right).
Since the proof of the Lagrange inversion formula is a very short computation, it is worth reporting one residue-based proof here (a number of different proofs exist,[6] using, e.g., Cauchy's coefficient formula for holomorphic functions, tree-counting arguments, or induction). Noting
\operatorname{ord}(f)=1
X\rightsquigarrowf(X)
\begin{align} k[Xk]gn& \stackrel{(v)
Generalizations. One may observe that the above computation can be repeated plainly in more general settings than K((X)): a generalization of the Lagrange inversion formula is already available working in the
\Complex((X))
X\alpha\Complex((X)),
f1=g1=1
m=-\alpha-\beta\in\N,
1 | |
\alpha |
[Xm]\left(
f | |
X |
| ||||
\right) |
[Xm]\left(
g | |
X |
\right)\beta.
For instance, this way one finds the power series for complex powers of the Lambert function.
Formal power series in any number of indeterminates (even infinitely many) can be defined. If I is an index set and XI is the set of indeterminates Xi for i∈I, then a monomial Xα is any finite product of elements of XI (repetitions allowed); a formal power series in XI with coefficients in a ring R is determined by any mapping from the set of monomials Xα to a corresponding coefficient cα, and is denoted . The set of all such formal power series is denoted
R[[XI]],
\left(\sum\alphac\alpha
\alpha\right)+\left(\sum | |
X | |
\alpha |
d\alphaX\alpha\right)=\sum\alpha(c\alpha+d\alpha)X\alpha
and
\left(\sum\alphac\alpha
\alpha\right) x \left(\sum | |
X | |
\beta |
d\beta
\beta\right)=\sum | |
X | |
\alpha,\beta |
c\alphad\betaX\alpha+\beta
The topology on
R[[XI]]
R[[XI]]
I=\N,
(fn)n\in
fn=Xn+Xn+1+Xn+2+ …
As remarked above, the topology on a repeated formal power series ring like
R[[X]][[Y]]
R[[X,Y]].
All of the operations defined for series in one variable may be extended to the several variables case.
In the case of the formal derivative, there are now separate partial derivative operators, which differentiate with respect to each of the indeterminates. They all commute with each other.
In the several variables case, the universal property characterizing
R[[X1,\ldots,Xr]]
\Phi:R[[X1,\ldots,Xr]]\toS
The several variable case can be further generalised by taking non-commuting variables Xi for i ∈ I, where I is an index set and then a monomial Xα is any word in the XI; a formal power series in XI with coefficients in a ring R is determined by any mapping from the set of monomials Xα to a corresponding coefficient cα, and is denoted
style\sum\alphac\alphaX\alpha
\left(\sum\alphac\alpha
\alpha\right)+\left(\sum | |
X | |
\alpha |
d\alpha
\alpha\right)=\sum | |
X | |
\alpha(c |
\alpha+d
\alpha | |
\alpha)X |
and multiplication by
\left(\sum\alphac\alpha
\alpha\right) x \left(\sum | |
X | |
\alpha |
d\alpha
\alpha\right)=\sum | |
X | |
\alpha,\beta |
c\alphad\betaX\alpha ⋅ X\beta
where · denotes concatenation of words. These formal power series over R form the Magnus ring over R.[7] [8]
\Sigma
S
S
\Sigma*
S\langle\langle\Sigma*\rangle\rangle
r:\Sigma*\toS
\Sigma*
\Sigma
The elements of
S\langle\langle\Sigma*\rangle\rangle
r=
\sum | |
w\in\Sigma* |
(r,w)w.
where
(r,w)
r
w\in\Sigma*
(r,w)\inS
r
For
r\inS\langle\langle\Sigma*\rangle\rangle
r
\operatorname{supp}(r)=\{w\in\Sigma*| (r,w) ≠ 0\}
A series where every coefficient is either
0
1
The subset of
S\langle\langle\Sigma*\rangle\rangle
S\langle\Sigma*\rangle
For
r1,r2\inS\langle\langle\Sigma*\rangle\rangle
s\inS
r1+r2
(r1+r2,w)=(r1,w)+(r2,w)
r1 ⋅ r2
(r1 ⋅ r2,w)=
\sum | |
w1w2=w |
(r1,w1)(r2,w2)
r1\odotr2
(r1\odotr2,w)=(r1,w)(r2,w)
sr1
r1s
(sr1,w)=s(r1,w)
(r1s,w)=(r1,w)s
With these operations
(S\langle\langle\Sigma*\rangle\rangle,+, ⋅ ,0,\varepsilon)
(S\langle\Sigma*\rangle,+, ⋅ ,0,\varepsilon)
\varepsilon
\Sigma*
These formal power series are used to model the behavior of weighted automata, in theoretical computer science, when the coefficients
(r,w)
w
See main article: Hahn series.
Suppose
G
<
a<b
a+c<b+c
c
G
\sumiaiXi
for all such I, with
ai
R
ai
R((G))
G
[[RG]]
R((G))
Various properties of
R
R((G))
R
R((G))
R
R((G))
G
R
R((G))
R
R((G))
This theory is due to Hans Hahn, who also showed that one obtains subfields when the number of (non-zero) terms is bounded by some fixed infinite cardinality.